1994
DOI: 10.1093/oxfordjournals.jbchem.a124688
|View full text |Cite
|
Sign up to set email alerts
|

An Extra Phosphorylation of Na+, K+-ATPase by Paranitrophenylphosphate (pNPP): Evidence for the Oligomeric Nature of the Enzyme1

Abstract: Paranitrophenylphosphate (pNPP) induced fluorescence changes in fluorescence isothiocyanate (FITC)-labeled Na+,K(+)-ATPase preparations. The extents of changes were similar to those induced by acetylphosphate (AcP) accompanying accumulation of a K(+)-sensitive phosphoenzyme (E2P) and an ouabain bound phosphoenzyme in the presence of Mg2+ and 16 mM Na+. Phosphoenzymes formed from [32P]pNPP were shown to turn over. The ratio of the maximum amount of the phosphoenzyme formed from pNPP to that of the phosphoenzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
1
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 0 publications
9
31
1
3
Order By: Relevance
“…27) to that of ouabain-enzyme complex. Present data are consistent with our previous data, which showed that the ratio of the maximum amount of ouabain-enzyme complex to that of phosphoenzyme was ϳ2 and was independent of the specific activity of the enzyme preparations from dog kidney purified with SDS (2000 -2750 mol of P i /mg of protein/h) or from pig kidney purified with sodium deoxycholate-NaI (500 -1200 mol of P i /mg of protein/h) (27). It has been reported that pig kidney Na ϩ ,K ϩ -ATPase preparations contained ϳ10% heterogeneity (38).…”
Section: Time Course Of Fluorescence Change and Phosphorylation Of Thsupporting
confidence: 93%
See 2 more Smart Citations
“…27) to that of ouabain-enzyme complex. Present data are consistent with our previous data, which showed that the ratio of the maximum amount of ouabain-enzyme complex to that of phosphoenzyme was ϳ2 and was independent of the specific activity of the enzyme preparations from dog kidney purified with SDS (2000 -2750 mol of P i /mg of protein/h) or from pig kidney purified with sodium deoxycholate-NaI (500 -1200 mol of P i /mg of protein/h) (27). It has been reported that pig kidney Na ϩ ,K ϩ -ATPase preparations contained ϳ10% heterogeneity (38).…”
Section: Time Course Of Fluorescence Change and Phosphorylation Of Thsupporting
confidence: 93%
“…The data showed that AP 2 PL modification and the AP 2 PL-FITC modification reduced the amount of phosphoenzymes from ATP to 50 and 6%, respectively, indicating that ϳ0.5 mol of AP 2 PL probe binding at Lys-480 and ϳ0.9 mol of FITC probe binding/␣-chain reduced the value (in moles of ATP-dependent phosphorylation/mol of ␣-chain) from 0.5 to 0.25 and 0.03 (Fig. 1B), with little influence on the half-site phosphorylation by AcP (Table I) and full-site ouabain binding in the presence of Mg 2ϩ and P i as reported previously (27). Stopped-flow measurements showed that the addition of 10 M ATP to the AP 2 PL enzyme and AP 2 PL-FITC enzyme preparations, respectively, in the presence of 4 mM Mg 2ϩ and 16 mM Na ϩ increased the AP 2 PL fluorescence intensity to ϳ3% despite 50 and 94% reduction in phosphorylation by ATP (Table I).…”
Section: Stoichiometry Of Phosphorylation Of Membrane-bound Nasupporting
confidence: 85%
See 1 more Smart Citation
“…In addition to ATP, the P-type pumps can hydrolyze other phosphate-containing substrates such as para-nitrophenyl phosphate [26,38,39,40], 3-O-methylfluorescein phosphate [41,42], and acetylphosphate [43,44]. We observed that eosin was a potent inhibitor of pNPPase activity (IC 50 = 3.8 ± 0.23 μM; Fig.…”
Section: Eosin Inhibition Of K + Activated Phosphatase Activitymentioning
confidence: 87%
“…Abbreviations: Cr(H20)4Adoi , i > [CH 2 ]i', ß,y bidentate complex of chromium(III)-tetraaqua-adenylyl [ß,y-methylene] diphosphonate; CofNHs^ATP, ß,y bidentate complex of cobalt(III)-tetramino-adenosine-5'-triphosphate; Co(NH3)4P04, tetramine cobalt(III)phosphate; FITC, fluorescein 5'isothiocyanate; NBD-C1, 7-chloro-4-nitrobenzo-2-oxa-l,3-diazole, 7-chloro-4-nitro-benzofurazane; EiATP site, nucleotide-binding site of Na + /K + -ATPase with high affinity for ATP; E2ATP site, nucleotide-binding site of Na + /K + -ATPase with low affinity for ATP phenomena of superphosphorylation from [y-32 P]ATP [4], double labeling with ATP analogs [5] or double phosphorylation from para-nitrophenylphosphate [6]. All these observations, including the observation of a positive cooperative effect of 2'-ODANS-8-N 3 -ATP in the inactivation of Na+/K+-ATPase [7] led to the conclusion that two simultaneously existing ATP sites need to cooperate during ATP-driven Na+/ K + transport [7,8].…”
Section: Introductionmentioning
confidence: 99%